Proceedings of the Health Science International Conference (HSIC 2017) 2017
DOI: 10.2991/hsic-17.2017.67
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Clean and Healthy Behavior and Quality of Life among School-Children

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 12 publications
0
10
0
10
Order By: Relevance
“…29 Forming clean and healthy living habits must be started from childhood by instilling good habit values to improve the quality of humans in the future. 30,31 The results of the study showed that there was no relationship between clean and healthy living habits and nutritional status. Physical activity is a series of body movements that use energy.…”
Section: Discussionmentioning
confidence: 93%
“…29 Forming clean and healthy living habits must be started from childhood by instilling good habit values to improve the quality of humans in the future. 30,31 The results of the study showed that there was no relationship between clean and healthy living habits and nutritional status. Physical activity is a series of body movements that use energy.…”
Section: Discussionmentioning
confidence: 93%
“…The data collection was administered by using a Clean and Healthy Behavior Scale (TCHBS) questionnaire from (Vionalita, 2017) with a Likert scale. The questionnaire had been tested for its validity and reliability.…”
Section: Methodsmentioning
confidence: 99%
“…The definition of health, according to the World Health Organization (WHO), is not only a condition of the absence of diseases and weaknesses, but also the presence of the balance function of physical, mental, and social aspects. Therefore, the life quality measurement related to health covers three functions, including physical aspects, psychological aspects (cognitive and emotional aspects), and social aspects (Vionalita, 2017). Meanwhile, healthy lifestyle promoting health includes activities which focus on the improvement of a person life wellbeing level.…”
Section: Introductionmentioning
confidence: 99%
“…Pengetahuan merupakan refleksi dari perilaku seseorang, pengetahuan yang baik dapat meningkatkan perilaku pada setiap orang (16) . Pemberian informasi terkait kebiasaan hidup sehat mulai dari usia sekolah dapat mempengaruhi perilaku hidup dan kualitas hidup pada anak (20) . Penelitian lain terkait PHBS pada anak usia sekolah ditemukan bahwa pengetahuan dan sikap berbanding terbalik dengan perilaku.…”
Section: Pembahasanunclassified
“…Perawat sekolah memiliki peran penting dan jangka panjang dalam meningkatkan status kesehatan anak usia sekolah (22) . Penelitian yang dilakukan oleh Vionalita dan Kusumaningtiar menjelaskan bahwa penting untuk memberikan informasi bagaimana cara dan praktik dari hidup bersih dan sehat dalam kehidupan nyata sejak kecil (20). Penelitian menjelaskan peran perawat sekolah dapat meningkatkan identifikasi dini risiko gangguan kesehatan pada anak.…”
Section: Pembahasanunclassified